Pengaruh Penerapan Pembelajaran Kooperatif Tipe TAI (Team Assisted Individualization) terhadap Kemandirian Belajar Akuntansi Siswa Kelas XII IPS MAS Ar-Rusydiny NW Segaet.: The Effect of Implementing TAI (Team Assisted Individualization) Type Cooperative Learning on Accounting Learning Independence of Class XII IPS Students MAS Ar-Rusydiny NW Segaet - Abd Quddus al Badani (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
Accounting is a service activity that provides quantitative information, especially financial information, about economic business entities in determining appropriate choices among various alternative actions. This study aims to determine the effect of the use of the TAI (Team Assisted Individualization) Cooperative Learning Model on the Independence of Accounting Learning of Class XII IPS Students of MAS Ar-Rusydiny NW Segaet. The type of research used is experimental research. The population is all students of class XII MAS Ar-Rusydiny NW Segaet totaling 93 people spread across three classes and the sample is class XII IPS II totaling 31 people. The determination of the sample uses cluster sampling, namely random sampling, the required clusters are taken by randomization. The research instrument used is a questionnaire with a total of 20 valid and reliable items. The results of data analysis show that the mean pre-test of student learning independence is 38.45 and the mean post-test is 40.32. This study uses the Chi-Square formula (χ2) to test data normality and the test results are then compared with the χ2 table. χ2 count for data normality test for control class of student learning independence is 5.80 while for experimental class is 9.69 with χ2 table is 11.10. Because χ2 count <χ2 table then the existing data is normally distributed. χ2 count for data homogeneity test is 0.34, while χ2 table for significance level of 5% is 3.84. Because χ2 count <χ2 table then the data is homogeneously distributed. While t count for data hypothesis test is 3.13 and t table for significance level of 5% is 1.67. Because t count> t table then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So it can be concluded that there is an influence of using Cooperative Learning Model Type TAI (Team Assisted Individualization) on Accounting Learning Independence of Class XII IPS MAS Ar-Rusydiny NW Segaet Students.